Environmental cost analysis to determine the effectiveness and efficiency of environmental activity control - Danial, Ahmad; Surbakti, Lidya Primta; Biswan, Ali Tafriji (Jurnalku, 2025)
This study aims to analyze the environmental costs incurred by PT Perusahaan Gas Negara Tbk. in controlling environmental activities from 2019 to 2023 and assess the effectiveness and efficiency of environmental cost control. The environmental costs analyzed consist of prevention costs, detection costs, internal failure costs, and external failure costs. The research method used is a qualitative analysis with a content analysis approach to the sustainability reports published by the company. The results show that although the company has implemented environmental activity control, the effectiveness of this control is still suboptimal, especially in 2022, where there was a significant increase in costs related to environmental management to comply with the PROPER policy. However, in overall, environmental cost control has been efficient, as indicated by the relatively small ratio of environmental costs to total operational costs. This study provides insights for the company to improve the effectiveness of environmental cost management, focusing on enhancing preventive activities to reduce failure costs that could harm the company in the future.